Rapamycin attenuates pathological hypertrophy caused by an absence of trabecular formation - Fleming, Nicole D; Samsa, Leigh A.; Hassel, David; Qian, Li; Liu, Jiandong (Scientific reports, 2018)
Cardiac trabeculae are mesh-like muscular structures within ventricular walls. Subtle perturbations in trabeculation are associated with many congenital heart diseases (CHDs), and complete failure to form trabeculae leads to embryonic lethality. Despite the severe consequence of an absence of trabecular formation, the exact function of trabeculae remains unclear. Since ErbB2 signaling plays a direct and essential role in trabecular initiation, in this study, we utilized the erbb2 zebrafish mutant as a model to address the function of trabeculae in the heart. Intriguingly, we found that the trabeculae-deficient erbb2 mutant develops a hypertrophic-like (HL) phenotype that can be suppressed by inhibition of Target of Rapamycin (TOR) signaling in a similar fashion to adult mammalian hearts subjected to mechanical overload. Further, cell transplantation experiments demonstrated that erbb2 mutant cells in an otherwise wildtype heart did not undergo hypertrophy, indicating that erbb2 mutant HL phenotypes are due to a loss of trabeculae. Together, we propose that trabeculae serve to enhance contractility and that defects in this process lead to wall-stress induced hypertrophic remodeling.
Gesehen am 22.04.2020